1991
DOI: 10.2136/sssaj1991.03615995005500010037x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Subsoil Compaction on Soil Strength and Plant Growth

Abstract: In recent years, scientists have become concerned that heavy farm equipment is causing soil compaction below the nominal depth of tillage. Compaction this deep may not be ameliorated after one season's freeze‐thaw and wet‐dry cycles. Experiments were conducted on a Kewaunee (fine, mixed, mesic Typic Hapludalf) and Rozetta (fine‐silty, mixed, mesic Typic Hapludalf) soil to determine the duration and effect of subsoil compaction on soil strength and corn (Zea mays L.) growth. Soil at two sites was compacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 0 publications
3
24
0
2
Order By: Relevance
“…The use of heavy machinery during restoration can be detrimental to soil properties and soil-regulated biotic processes (Lowery andSchuler 1991, Kozlowski 1999). Fangueo is a form of mechanical disturbance that at Palo Verde Marsh entails the use of a tractor.…”
Section: Discussionmentioning
confidence: 99%
“…The use of heavy machinery during restoration can be detrimental to soil properties and soil-regulated biotic processes (Lowery andSchuler 1991, Kozlowski 1999). Fangueo is a form of mechanical disturbance that at Palo Verde Marsh entails the use of a tractor.…”
Section: Discussionmentioning
confidence: 99%
“…The drained pore volume [24] and hydraulic conductivity under saturated conditions [22,11] are both seen to decrease while the penetration resistance increases [6,15]. Consolidation of a soil reduces its aeration, increases its mechanical strength and restricts the length and density of roots [1,25].…”
mentioning
confidence: 99%
“…Although tractor use has the potential to alter soil and seed bank properties (Froud-Williams et al 1984;Lowery and Schuler 1991;Kozlowski 1999), a concurrent study found no short-term impact of fangueo on several soil and seed bank properties in Palo Verde Marsh (Osland et al 2011).…”
Section: Experimental Designmentioning
confidence: 96%